Progress and Prospect of Immunotherapy for Triple-Negative Breast Cancer - Luo, Chenyi; Wang, Peipei; He, Siqi; Zhu, Jingjing; Shi, Yuanyuan; Wang, Jianxun (Frontiers in Oncology, 2022)
Breast cancer is the most commonly diagnosed cancer (estimated 2.3 million new cases in 2020) and the leading cause of cancer death (estimated 685,000 deaths in 2020) in women globally. Breast cancers have been categorized into four major molecular subtypes based on the immunohistochemistry (IHC) expression of classic hormone and growth factor receptors including the estrogen receptor (ER), progesterone receptor (PR), and human epidermal growth factor receptor 2 (HER2), as well as a proliferation marker Ki-67 protein expression. Triple-negative breast cancer (TNBC), a breast cancer subtype lacking ER, PR, and HER2 expression, is associated with a high metastatic potential and poor prognosis. TNBC accounts for approximately only 15%–20% of new breast cancer diagnoses; it is responsible for most breast cancer–related deaths due to the lack of targeted treatment options for this patient population, and currently, systemic chemotherapy, radiation, and surgical excision remain the major treatment modalities for these patients with TNBC. Although breast cancer patients in general do not have a robust response to the immunotherapy, a subset of TNBC has been demonstrated to have high tumor mutation burden and high tumor-infiltrating lymphocytes, resembling the features observed on melanoma or lung cancers, which can benefit from the treatment of immune checkpoint inhibitors (ICIs). Therefore, the immunogenic nature of this aggressive disease has presented an opportunity for the development of TNBC-targeting immunotherapies. The recent US Food and Drug Administration approval of atezolizumab in combination with the chemotherapeutic agent nab-paclitaxel for the treatment of PD-L1-positive unresectable, locally advanced, or metastatic TNBC has led to a new era of immunotherapy in TNBC treatment. In addition, immunotherapy becomes an active research area, both in the cancer biology field and in the oncology field. In this review, we will extend our coverage on recent discoveries in preclinical research and early results in clinical trials from immune molecule-based therapy including cytokines, monoclonal antibodies, antibody–drug conjugates, bi-specific or tri-specific antibodies, ICIs, and neoantigen cancer vaccines; oncolytic virus-based therapies and adoptive immune cell transfer–based therapies including TIL, chimeric antigen receptor-T (CAR-T), CAR-NK, CAR-M, and T-cell receptor-T. In the end, we will list a series of the challenges and opportunities in immunotherapy prospectively and reveal novel technologies such as high-throughput single-cell sequencing and CRISPR gene editing-based screening to generate new knowledges of immunotherapy.